Impact of Intervention on Reduction of White Blood Cells in the Management of Infection in Pneumonia Patients - Aryanda, Sri; Nasution, Azizah; K, Khairunissa (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: To study the impact of intervention on the reduction of white blood cells (WBC) in the management of infection in patients with pneumonia in Universitas Sumatera Utara (USU) hospital period July through September 2019. Method: This three-month analytical prospective cohort study analyzed the reduction of WBC in the management of infection in pneumonia patients (n=42) before and after intervention in USU hospital. A self-designed questionair was used to assess the patients characterics, the required laboratory data including WBC, and length of stay (LOS). The base-line data were assessed after three days of treatment. The data with intervetion were assessed between July - September 2019. The Patients characteristics and drug utilization were analyzed descriptively. The levels of WBC before and after interventions were compared using paired samples t test (p < 0.05) was considered significant. Results: Characteristics of the pneumonia patients: male, 61.9%; female, 38.1%. The mean age of patients with pneumonia was 60.48 ± 14.76 years. The most widely used antibiotic was ceftriaxone as much as 48%. There was a significant difference in reduction of WBC between patients with pneumonia before and after intervention, p= 0.002. Conclusions: Intervention can significantly increase the treatment of infection in patients with pneumonia.